2019
DOI: 10.1186/s13148-019-0786-y
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 recruited by EZH2-mediated silencing of miR-484 contributes to the malignancy of cervical cancer cells through MMP14 and HNF1A

Abstract: BackgroundEmerging evidence indicates that dysregulation of microRNAs (miRNAs) contributes to cervical cancer (CC) tumorigenesis and development. Previous work showed that miR-484 which regulated the EMT process was obviously downregulated in CC. However, little is known about the precise mechanism.ResultsWe found that the deficiency of EZH2-recruited DNA methyltransferases DNMT1 reduced the CpG methylation of miR-484 promoter and then increased the miR-484 expression. Furthermore, the cell membrane-bound matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…miRNA is a type of non-coding small RNA molecule, which has emerged as a critical molecular marker in development and progression of many cancers [43,44]. For instance, silencing of miR-484 could aggravate the malignancy of cervical cancer cells by inhibiting MMP14 and HNF1A [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA is a type of non-coding small RNA molecule, which has emerged as a critical molecular marker in development and progression of many cancers [43,44]. For instance, silencing of miR-484 could aggravate the malignancy of cervical cancer cells by inhibiting MMP14 and HNF1A [43].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is a type of non-coding small RNA molecule, which has emerged as a critical molecular marker in development and progression of many cancers [43,44]. For instance, silencing of miR-484 could aggravate the malignancy of cervical cancer cells by inhibiting MMP14 and HNF1A [43]. In addition, it was observed that exosomal miR-106b increased the MMP-2 and MMP-9 expression, leading to an enhancement of the migration and invasive ability of BEAS-2B cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, MMP14 and MMP16 also play important roles in the development of multiple tumors. [17][18][19][20] However, whether miR-26a regulates MMPs in CSCC remains elusive. The purpose of our study was to clarify the specific function of miR-26a in CSCC and to further clarify the regulation of miR-26a on MMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Furtherly, our results suggested that knockdown EZH2 could retort the UCA1-induced upregulation of p-PI3K and p-AKT. In addition, one-fifth of all human lncRNAs identified is physically associated with EZH2 [20,21]. To determine the association between UCA1 and EZH2, RIP and RNA pull down assay were performed.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is a crucial component of PRC2, which was reported physically associated with one-fifth of lncRNAs to date [20,21]. We postulated that UCA1 may interact with and bind to EZH2 to regulate downstream molecular events in view of the regulation of UCA1 on EZH2 protein expression.…”
Section: Uca1 Directly Interact With Ezh2 In Gastric Cancer Cellmentioning
confidence: 96%